(untitled) (Journal of Management and Business Education, 2019)
This research, titled by the author as Inspiring Education, encompasses a broad, free and useful term for the human being, providing elements and indicators to create awareness and improve current education. It intends to prepare students, teachers, leaders and human beings to acquire and apply knowledge to think and find solutions in favor of ethical, productive and happier achievements. Three main components have combined: First, an electronically applied questionnaire, answered anonymously which integrates demographic and key questions to determine necessary and useful categorizations or indicators to achieve a better education according to the criteria and perception of the sample. The research is descriptive, combining quantitative and qualitative design. The sample was composed of 309 professionals and educators from the state of Baja California, Mexico, which borders the state of California, U.S.; secondly, the Inspiring Education evaluation of indicators presented to the sample and coming from previous results. Third, the results from the literature review. The combination of these three components helps identify and understand the existing reality in education and suggests improvements that significantly contribute to education in a comprehensive and inclusive manner.